Assessment of the Degree of Involvement of Russians in Enlightenment Projects - L.N. Dukhanina; A.A. Maksimenko (Moscow State University of Psychology and Education, 2024)
The article deals with the issues of involvement of Russian society in the enlightenment projects in present day. The material is based on the results of an online survey of 1213 respondents (54,7% men, 43,3% women), dedicated to assessing the degree of awareness of Russians about existing enlightenment platforms and projects implemented in recent years. As part of the survey, the degree of involvement of respondents in enlightenment projects was recorded based on the identification of the first mentioned (top-of-mind) enlightenment project (knowledge without a hint), knowledge of enlightenment projects with a hint was determined, and the depth for immersion in an enlightenment container and preparation was measured, it is recommended to use one or another enlightenment product. The key channels of perception of advertising information about the main enlightenment projects implemented in the media and network space of Runet were also digitized. According to the data obtained, 53,8% of the respondents could not name a single project on their own (without prompting), more than 13% noted enlightenment projects in social networks and 7% – projects on TV (excluding projects of the TV channel "Culture"). With the induced knowledge, 81,3% of respondents noted enlightenment projects of the TV channel "Culture" (81,3% of respondents replied that they were aware of this project), projects of the Russian Society "Knowledge" (36,6%), and Arzamas platforms (28%). Only 20% of respondents, on average, will see the enlightenment content to the end. Half of the respondents are not ready to recommend any of the projects (or do not know about them), while 22,9% express loyalty to the TV channel "Culture", but on average less than 10% of respondents are ready to recommend the remaining sites. Based on the data obtained, the authors conclude about the quality of enlightenment projects as an indirect indication of the depth of immersion in enlightenment content and the willingness to recommend this or that enlightenment project to their colleagues and/or acquaintances, friends.